ASSESSING STUDENT’S ANXIETY ON SPEAKING AT JUNIOR HIGH SCHOOLS IN SOUTHWEST ACEH - Rizki Adinda Mira; Nuzulul Isna (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this research is to investigate the level of students’ anxiety students in speaking performance in class. This study used a quantitative cross-sectional design. 157 participants from SMPN 2 Susoh and SMPN 1 Jeumpa in Southwest Aceh participated in the study. 100 data point was analyzed descriptively through SPPS software. Oetting’s (1983) scale of students’ anxiety level in speaking Performance. The result and discussions were presented further in the study. in class.